Medium-term storage of platelet-derived orthobiologics: a feasible alternative for equine practice - Seidel, Sarah Raphaela Torquato; Fülber, Joice; Barbosa, Ângela Perrone; Penatti, Natalia Mori Avellaneda; Demasi, Marilene; Baccarin, Raquel Yvonne Arantes (Frontiers in Veterinary Science, 2026)
IntroductionPlatelet-rich plasma (PRP) is commonly used by equine veterinarians. Although PRP is considered a feasible and affordable orthobiologic, its use has been associated with certain drawbacks, such as the time required for protocols and the necessity of using a fresh product, which is usually prepared at the time of use. In this context, the present study aimed to produce PRP-derived orthobiologics with the potential to be stored for longer periods while maintaining similar growth factor contents.MethodsPRP was prepared from six donors and subjected to additional processing: lysis, yielding Platelet Lysate (PL), and freeze-drying, yielding lyophilized PRP (FD-PRP). The three products were stored for 30 days at different temperatures (−80°C, −20°C, and room temperature [RT]). Additionally, orthobiologics from a single donor were also subjected to longer periods of storage: PRP, FD-PRP, and PL for 1 and 2 years at −80°C and −20°C; and FD-PRP at RT was stored for 1 year with cryoprotectant and 30 days without cryoprotectant.ResultsStorage for 30 days presented distinct pattern related to the temperatures on each orthobiologic: there was no difference on TGF-β1 concentrations between the hemocomponents at −80°C, PL retained a high TGF-β1 concentration at −20°C, PRP and FD-PRP showed a slight increase in TGF-β1 content at RT when compared to PL. RT also resulted in decreases in IL-1β, IL-10, and TNF-α concentrations in all hemocomponents.DiscussionThe protocols used in this study efficiently produced hemocomponents with similar content, offering some benefits, such as the possibility of preparing major volumes at the same time, preparing aliquots that would be ready to be used throughout the entire treatment, and storing them in farms, clinics, and hospitals.